The accidental capitalist : a people's story of the new China - Yaghmaian, Behzad, 1953- (Pluto Press, 2012)
"In the last three decades China has experienced the largest population movement in human history. Millions have left behind homes to find work and new opportunities in the emerging mega-cities. Through months of sustained interpersonal contact with migrant workers and factory owners, Behzad Yaghmaian paints a unique portrait of a country experiencing the turmoil of rapid development. His close listening has produced an intimate look at the hopes, hardships, triumphs and tragedies of those behind the Chinese 'economic dragon'. The Accidental Capitalist reveals the human reality behind China's rise to global-superpower status. Yaghmaian articulates the collective narrative of a people which will resonate with anyone living under capitalism and provide valuable material to students and scholars"--Pub. descr